Gender Differences in Burnout Among Endocrinologists in China - Wang, Jing; Zhang, Lufa; Jiang, Feng; Liu, Yuanli; Wang, Mingxiao; Wu, Yinuo; Tang, Yi-Lang (Frontiers in Psychology, 2022)
Objective: To survey the prevalence of burnout in a national sample of endocrinologists in China and to examine its correlates, with a special focus on gender differences. Methods: An anonymous online survey was conducted among endocrinologists in government-owned hospitals. Demographic and work-related factors were collected from participants. The Maslach Burnout Inventory-Human Services Survey (MBI-HSS) was used to assess burnout. Results: A total of 711 endocrinologists (72.1% were female) completed the survey. Burnout was reported by 32.8% of the participants. There were no significant gender differences in the overall prevalence of burnout or EE, DP, and PA (all p >0.05). A multi-level linear regression revealed: (1) In male participants, PA was significantly associated with age (=0.03, p=0.003), DP was inversely associated with age (=-0.06, p=0.005), EE was significantly associated with shorter sleep duration (=-0.25, p=0.006), and longer work hours (=0.01, p=0.016). (2) In females, PA was significantly associated with age (=0.01, p=0.038), EE and DP were both significantly associated with shorter sleep duration (=-0.19, p=0.001; and =-0.15, p=0.011 respectively). EE and DP were also associated with work hours (=0.02, p<0.001; and =0.01, p<0.001, respectively). Conclusion: Nearly one-third of endocrinologists in China experienced burnout. Although there were no significant gender differences in the prevalence of overall burnout or EE, DP, and PA scores, male and female participants differed in factors associated with EE, DP and PA. Interventions need to be tailored to target different aspects in male and female endocrinologists and target different subgroups.